2019
DOI: 10.1002/ehf2.12516
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance and albuminuria in patients with chronic heart failure: a subanalysis of the SUPPORT trial

Abstract: AimsThe study aims to evaluate the prognostic significance of impaired glucose tolerance (IGT) with reference to albuminuria in patients with chronic heart failure (CHF). Methods and resultsWe examined 535 CHF patients (mean 66years, women 25%) in the control arm of our SUPPORT trial, in which we examined additive impact of olmesartan in hypertensive patients with symptomatic CHF treated with β-blockers and/ or angiotensin-converting enzyme inhibitors. We examined the association between glycaemic abnormality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…18 Second, in patients with HF with prediabetes, further However, in those without albuminuria, the risk of mortality was similar in those with IGT or normoglycaemia. 17 Third, our results emphasized the importance of better understanding of the role across a broader range of glucometabolic abnormalities in HF, achieving timely and effective prevention of adverse outcomes. Optimal management of prediabetes in HF remains to be defined.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…18 Second, in patients with HF with prediabetes, further However, in those without albuminuria, the risk of mortality was similar in those with IGT or normoglycaemia. 17 Third, our results emphasized the importance of better understanding of the role across a broader range of glucometabolic abnormalities in HF, achieving timely and effective prevention of adverse outcomes. Optimal management of prediabetes in HF remains to be defined.…”
Section: Discussionmentioning
confidence: 79%
“…13,14 However, whether prediabetes is associated with a worse prognosis in patients with HF remains unclear. [15][16][17][18] Therefore, in this meta-analysis, we aimed to answer the following question: in patients with established HF, does coexisting prediabetes confer a worse prognosis than in those with normoglycaemia?…”
mentioning
confidence: 99%
“…Diabetic microangiopathy is associated with an increased risk of HF and can be assessed by using the urine albumin-to-urine creatinine ratio (uACR). It has been demonstrated that albuminuria was closely related to the occurrence, development, and prognosis of CHD and HF [7][8][9][10]. A community-based study also confirmed that the risk of HF was increased by 54-91% with a mild increase in uACR [11].…”
Section: Introductionmentioning
confidence: 81%
“…In a series of 227 HFrEF patients who had an OGTT, 23% were classified as having IGT and 18% as having newly diagnosed diabetes, and similar percentages were found in patients with either ischemic or non-ischemic HF [ 7 ]. In a subanalysis of the SUPPORT trial including 535 HF patients without known diabetes (18% with HFrEF and 62% with HFpEF), IGT was found in 23% of those participants [ 32 ]. However, there was no published study comparing adequately the prevalence of newly diagnosed glucose disorders in HFrEF and HFpEF patients.…”
Section: Discussionmentioning
confidence: 99%